PENGARUH PRODUK, HARGA, DAN PROMOSI TERHADAP MINAT BELI DITOKO BANJAR MART DESA PETALING KABUPATEN BANGKA - Rika Lestari; Siti Napisah; Rahmad Firdaus; Andy Yusfany (LPPM STIE PERTIBA Pangkalpinang, 2023)
This study aims to determine the effect of product, price, promotion on buying interest at the Banjar Mart store, Petaling village, Bangka Induk Regency. This research is a quantitative research, so the data collection that will be used in the research is done by using a questionnaire that will be filled out directly by the respondent. This study uses multiple linear regression analysis, the result of which is that it is known that the variables of product, price, promotion on buying interest at the Banjar Mart store, Petaling Village, Bangka parent district. The results of the F test show that the calculated F is 34,720> F table 2.70 with a significance level of 0.000 0.05. This shows that the independent variables are product, price. and promotion together proved to have a significant effect on buying interest. The t-test aims to show how far the influence of one independent variable or independent variable (X) individually in explaining the variation of the dependent variable or the dependent variable (Y). The coefficient of determination (R Square) is 0.531, which means 53.1% of the independent variables are able to explain the effect on the dependent variable, while 46.9% is influenced by other independent variables not included in the study.